Life-cycle and sustainability of civil infrastructure systems : proceedings of the Third International Symposium on Life-Cycle Civil Engineering, Hofburg Palace, Vienna, Austria, 3-6 October 2012 /: proceedings of the Third International Symposium on Life-Cycle Civil Engineering, Hofburg Palace, Vienna, Austria, 3-6 October 2012. (©2013) - Unknown
No abstract available